Infrared Spectroscopic Analysis of Sub-Monolayer Perfluoropolyether Films Based on the —[(CF2)nO]– Monomer Unit for n = 2, 3 and 4 - Robert J. Waltman (Japanese Society of Tribologists, 2014)
Infrared specular reflection spectra of the TA-30, D-4OH and C4-4OH perfluoropolyether liquid films on gold substrates are simulated and studied experimentally. The simulated spectra were obtained using a classical dispersion analysis coupled with solutions of Maxwell's equations for transmission and reflection of electromagnetic radiation. The simulated spectra, which are based on a randomly oriented sample, provide excellent fits for the perfluoropolyethers over a wide film thickness range. Spectroscopic data are provided for TA-30, D-4OH and C4-4OH. The differences in the transverse and longitudinal optical IR spectra are discussed for off-normal reflection spectra in the thin film limit. Corrections to the IR reflection spectra for sub-monolayer coverage using effective medium theory are also discussed.